Effect of the antral follicle count of Bos taurus × Bos indicus dairy cows on in vitro embryo production - Garcia, Sheila Merlo; Lunardelli, Paula Alvares; Ancioto, Kleber Luciano; de Oliveira, Eduardo Cardoso [UNESP]; Bergamo, Larissa Zamparone; Zangirolamo, Amanda Fonseca; Seneda, Marcelo Marcondes (Universidade Estadual de Londrina, 2020)
This study aimed to evaluate the potential of Girolando (Bos taurus × Bos indicus) cows with high and low antral follicle counts (AFC) for the in vitro production of bovine embryos (IVEP), as well as the pregnancy rates of the recipients of these embryos. Girolando cows (Bos taurus × Bos indicus) were classified as high and low AFC when they had 35-52 (n = 13) and 11-17 follicles (n = 15), respectively. All animals were subjected to repeated follicular aspiration [Ovum pick-up (OPU)] and subsequent IVEP sessions. The synchronization protocol of the recipients was performed on a random day of the estrous cycle (Day 0) with the implantation of progesterone, estradiol benzoate, and prostaglandin. The high AFC group had higher aspirated oocyte/OPU (42.6 ± 5.2 vs. 14.6 ± 1.9; p < 0.01) and cultured oocyte/OPU (38.1 ± 6.6 vs. 12.3 ± 2.8; p < 0.01) averages as well as a higher blastocyst percentage on D7 (23.0 ± 1.0% vs. 18.4 ± 1.5%; p < 0.05) and higher pregnancy rate (42.7 ± 2.7% vs. 39.7 ± 4.6%; p < 0.05) than the low AFC group. Thus, we can conclude that animals with high AFC had better IVEP success rates than animals with low AFC.
Efeito da contagem de folículos antrais de vacas Bos taurus x Bos indicus com aptidão leiteira na produção in vitro de embriões
Keywords: AFC; Bos taurus × Bos indicus; Embryo production; OPU